Descender. Volume 6, The machine war - Lemire, Jeff (Image Comics, 2018)
"All the various factions that have been hunting TIM-21 finally converge around the ocean planet Mata, just as the robots launch their galaxy-wide revolution. But nothing can prepare the young android Tim--or the readers--for what happens next. This climactic chapter...brings the Descender saga to a close and sets the stage for the next mind-bending adventure."--Page 4 of cover